The Lack of Legal Regulations in Handling Inter-Community Brawls and the Urgency of Legal Reform Based on Preventive and Restorative Approaches - Agus Adi Wijaya; Binsar Jon Vic S. (Journal of Legal and Cultural Analytics, 2026)
This study aims to analyze the gaps in legal regulations regarding the handling of brawls between community groups and to formulate a direction for legal reform based on preventive and restorative approaches. The method employed is a normative juridical approach, incorporating statutory and conceptual elements, based on a review of the Criminal Code, Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, and other related regulations. The results indicate that positive law does not specifically regulate brawls as a form of collective violence, resulting in a normative gap in definitions, collective criminal liability, and conflict prevention and resolution mechanisms. This gap has resulted in ineffective law enforcement, characterized by inconsistent norm application, the dominance of repressive approaches, and a failure to break the cycle of violence. Therefore, a reconstruction of legal reform is needed, including the reformulation of legal norms, strengthening preventive approaches through multi-stakeholder involvement, and the development of restorative mechanisms that emphasize the restoration of social relations. This reform is expected to create a more responsive, adaptive, and equitable legal system in addressing brawls as a structural social problem.